Astringency quantification in wine: comparison of the electronic tongue and FT-MIR spectroscopy - Simoes Costa, Ana Maria
Electronic tongue based on potentiometric chemical sensors and Fourier transform mid-infrared spec-troscopy (FT-MIR) were evaluated as rapid tools for the prediction of gelatin index of red, white and rosewines. Gelatin index was measured using modified procedure, which was applicable not only to red butalso to white and rose wines. Relationship between gelatin index and a set of chemical parameters, elec-tronic tongue and FT-MIR data have been investigated using multi-block analysis method called commoncomponent and specific weight analysis (CCSWA). Calibration models for gelatin index prediction werecalculated using partial least square (PLS) regression. Variable selection for the PLS models was doneusing Variable Importance in Prediction criterion. Quantification of gelatin index in red and rose winewas possible using both electronic tongue and FT-MIR data with adjusted R2in prediction of 0.75 and0.89 for rose and 0.83 and 0.87 for red wine, respectively.